The Gender-Specific Effect of Working Hours on Family Happiness in South Korea - Robert Rudolf; Seo-Young Cho (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2011)
This paper uses detailed longitudinal data from the Korean Labor and Income Panel Study (KLIPS) stretching from 1998 to 2008 to analyze the relationship between working hours and family happiness in Korea. The Korean labor market is characterized by high levels of gender inequality which is partly due to long working hours, a significant gender gap in earnings, yet also to traditional gender roles maintained until today. Therefore, post-marriage labor force participation rates for men are still double as high as for women. However, significant changes took place over the period of our study. Working hours have been steadily reduced and female labor force participation slightly increased, partly due to the introduction of the 5-day working week in 2004. Hours, job, and life satisfaction have all increased hence. Running fixed-effects ordered logit models on married couples with children, we analyze hours, job, and life satisfaction separately for women and men. Our findings indicate that past working hours reductions increased family happiness in Korea. However, there are still strong gender-specific effects how working hours affect family happiness. Controlling for household income, wives report highest satisfaction when either not-working or working 31 to 40 hours per week. Both part-time and overtime work reduce women's happiness. Korean husbands, in comparison, are best off when being full-time employed with weekly working hours between 31 and 50. Staying at home or being only part-time employed (1-30 hours) is strongly detrimental to their happiness. For both sexes, cross-partner effects are strongly significant. These findings are particularly interesting in comparison to other countries like Great Britain or Australia where similar studies were carried out (Booth and van Ours, 2008; 2009). Results confirm strong traditional gender roles in Korea until today. In order to further increase female labor force participation and family happiness, further reductions in working hours should be flanked by policies promoting equal chances at the work place, a rethinking of gender identities, and flexible job and child-care solutions.
Keywords: I31; J22; J16; J28; 330; Working hours; Happiness; Gender identity; Female labor force participation